New Tax On Leaf Denounced (Tufts Archival Research Center, 2007)
News clipping from The Durham Sun in Durham, North Carolina concerning a proposed cigarette tax ranging from 2 to 50 cents per pack, depending on relative tar and nicotine content. Explains a proposed tax might result in fewer high tar and nicotine cigarettes purchased, thus preventing some of the cancers otherwise caused by smoking. Summarizes the industry's argument that there is no clear evidence linking tobacco and cancer, and that the proposed tax would hit blue collar workers the hardest.